2011
DOI: 10.1007/s00027-011-0242-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use on water column bacterial activity and enzyme stoichiometry in stream ecosystems

Abstract: Fifty streams, located in southern Ontario, Canada, were visited in September 2008 to investigate the effect of varying land use, land cover, and associated resource inputs on water column bacterial abundance (BACT), production (BP), and extracellular enzyme activity and stoichiometry. Principle components analysis was used to summarize landscape data, producing three components (PCs), which explained 79.2% of the variability in the data. The PCs grouped into the following gradients: (PC1) urban land use and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
(71 reference statements)
1
12
3
1
Order By: Relevance
“…Williams et al (58) found that this ratio approaches 1:1 with increased levels of dissolved organic C and dissolved organic N. In our study, the LAP/AP ratios were 1:50 at J2482 and 1:20 at J2477. Greater AP activity in this study can be interpreted as a higher demand for phosphorus and/or carbon.…”
Section: Discussionsupporting
confidence: 59%
“…Williams et al (58) found that this ratio approaches 1:1 with increased levels of dissolved organic C and dissolved organic N. In our study, the LAP/AP ratios were 1:50 at J2482 and 1:20 at J2477. Greater AP activity in this study can be interpreted as a higher demand for phosphorus and/or carbon.…”
Section: Discussionsupporting
confidence: 59%
“…In general, forested streams (specifically Fuirosos) are primarily heterotrophic, with the DOM in the stream water primarily resulting from allochthonous sources (Thurman 1985;Butturini et al 2008). Higher enzyme activities in water with nutrient enrichment have also been observed (Williams et al 2012), but the temporal differences observed in our study are not related to light, as observed for biofilms.…”
Section: Biochemical Quality Of the Suspended And Dissolved Omcontrasting
confidence: 44%
“…The land cover and use in the catchments is a mix of forests, wetlands and agriculture and to a lesser extent developed (urban or suburban) land (see Supplemental Table 1 and Wilson & Xenopoulos ; Williams et al . for detailed watershed characteristics). Freshwater mussel populations, while somewhat ubiquitously distributed, are often observed as patches (~100 m long) called ‘mussel beds.’ Therefore, using an unpublished Fisheries and Oceans Canada database, site selection was initially filtered according to the presence of either or both focal mussel species E. complanata (Lightfoot 1786) and L. costata (Rafinesque 1820) (~80–90 sites), and then refined according to the desired range of agriculture intensity, watershed area and proximity to laboratory.…”
Section: Methodsmentioning
confidence: 99%